Correlational between Habit of Watching Movie and Speaking Mastery - Ramadhani Hutagaol, Ingrid Nauli; Lubis, Fitriadi; Siregar, Sri Rahmadhani (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research is intended to investigate the correlation between students‟ habit of watching movie and their speaking mastery. This research used quantitative research with the correlational research type. The sample of this research was 33 students from the fifth semester of English department UIN Syekh Ali Hasan Ahmad Addary Padangsimpuan. The data was collected using questionnaire and test and analyzed by using product moment test. The finding of this research showed that there was a correlation between habit of watching movie and speaking in average category with the calculation rcount ˃ rtable (0.566 ˃ 0.339). Therefore the test of t-test showed that alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. It can be conclude that there was a significant correlation between habit of watching movie and speaking mastery at the fifth semester of English department UIN Syahada Padangsidimpuan